Assessment of Safety and Efficacy of Combined Trabectedin and Low-Dose Radiotherapy for Patients With Metastatic Soft-Tissue Sarcomas: A Nonrandomized Phase 1/2 Clinical Trial - Martin-Broto, Javier (JAMA Oncol, 2020)
IMPORTANCE: Active therapeutic combinations, such as trabectedin and radiotherapy, offer potentially higher dimensional response in second-line treatment of advanced soft-tissue sarcomas. Dimensional response can be relevant both for symptom relief and for survival. OBJECTIVE: To assess the combined use of trabectedin and radiotherapy in treating patients with progressing metastatic soft-tissue sarcomas. DESIGN, SETTING, AND PARTICIPANTS: Phase 1 of this nonrandomized clinical trial followed the classic 3 + 3 design, with planned radiotherapy at a fixed dose of 30 Gy (3 Gy/d for 10 days) and infusion of trabectedin at 1.3 mg/m(2) as the starting dose, 1.5 mg/m(2) as dose level +1, and 1.1 mg/m(2) as dose level –1. Phase 2 followed the Simon optimal 2-stage design. Allowing for type I and II errors of 10%, treatment success was defined as an overall response rate of 35%. This study was conducted in 9 sarcoma referral centers in Spain, France, and Italy from April 13, 2015, to November 20, 2018. Adult patients with progressing metastatic soft-tissue sarcoma and having undergone at least 1 previous line of systemic therapy were enrolled. In phase 2, patients fitting inclusion criteria and receiving at least 1 cycle of trabectedin and the radiotherapy regimen constituted the per-protocol population; those receiving at least 1 cycle of trabectedin, the safety population. INTERVENTIONS: Trabectedin was administered every 3 weeks in a 24-hour infusion. Radiotherapy was required to start within 1 hour after completion of the first trabectedin infusion (cycle 1, day 2). MAIN OUTCOMES AND MEASURES: The dose-limiting toxic effects of trabectedin (phase 1) and the overall response rate (phase 2) with use of trabectedin plus irradiation in metastatic soft-tissue sarcomas. RESULTS: Eighteen patients (11 of whom were male) were enrolled in phase 1, and 27 other patients (14 of whom were female) were enrolled in phase 2. The median ages of those enrolled in phases 1 and 2 were 42 (range, 23-74) years and 51 (range, 27-73) years, respectively. In phase 1, dose-limiting toxic effects included grade 4 neutropenia lasting more than 5 days in 1 patient at the starting dose level and a grade 4 alanine aminotransferase level increase in 1 of 6 patients at the +1 dose level. In phase 2, among 25 patients with evaluable data, the overall response rate was 72% (95% CI, 53%-91%) for local assessment and 60% (95% CI, 39%-81%) for central assessment. CONCLUSIONS AND RELEVANCE: The findings of this study suggest that the recommended dose of trabectedin for use in combination with this irradiation regimen is 1.5 mg/m(2). The trial met its primary end point, with a high overall response rate that indicates the potential of this combination therapy for achieving substantial tumor shrinkage beyond first-line systemic therapy in patients with metastatic, progressing soft-tissue sarcomas. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT02275286